Deciphering the Sharia Legal Framework Issues in Islamic Financial Institutions in Indonesia - et al., Dece Kurniadi (International Journal of Advanced Science and Technology, 2019)
Sharia financial institutions currently operate based on fatwa and  Financial Services Authority Regulation (POJK) as well as positive laws that apply in Indonesia. However, the basic problem is the absence of a good sharia legal framework that can be monitored, regulated and supervised. This study aims to parse more deeply on the problems of the sharia legal framework seen from internal and external angles. In addition to elaborating on the main problem, this study also aims to get the right solution and what strategies are taken by all stakeholders so that the Sharia legal framework in Islamic financial institutions can be implemented properly. Therefore, to get the good results, this study conduct a literature review that can be applied not only to root the problem of a study but also to provide accurate solutions and strategies. This study is expected to have implications for the implementation of Sharia audits, governance and Shariah standards that can be applied by all LKS (Islamic Financial Institution). Related parties will play an active role with the implementation of Islamic Sharia legal frameworks that are certain and provide a stimulus for a positive contribution to the Sharia finance industry in Indonesia.